Effects of 1,25-dihydroxycholecalciferol and reduced vitamin D-3 level on broiler performance and bone quality - Souza Castro, Fernanda Lima de; Baiao, Nelson Carneiro; Ecco, Roselene; Quirino Louzada, Mario Jefferson [UNESP]; Melo, Erica de Faria; Saldanha, Mariana Masseo; Triginelli, Marcela Viana; Camargos Lara, Leonardo Jose (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
This study was conducted to evaluate the effect of two levels of vitamin D-3 with or without 1,25-dihydroxycholecalciferol (1,25(OH)(2)D-3) on live performance and bone quality of broiler chickens. For that, we used a completely randomized design in a 2 x 2 factorial arrangement, with eight replicates of 30 Cobb (R) 500 male broiler chicks each (n = 960). The two levels of vitamin D-3 and the addition or not of 0.5 mu g 1,25(OH)(2)D-3/kg were considered as main factors. The vitamin D-3 levels were: 2500/2000 IU/kg and 1250/1000 IU/kg for the starter (1 to 21 days) and grower (22 to 40 days) phases, respectively, with the first representing the levels used in industry (100%) and the second, a reduction in 50% of those levels. The 1,25(OH)(2)D-3 source was Solanum glaucophyllum. On days 21 and 40, one broiler per replicate was killed and long bones were removed for analyses of mineral percentage, bone mineral density, biomechanical properties, and morphology. No significant differences were found related to vitamin D-3 levels and the addition or not of 1,25(OH)(2)D-3 for live performance, mineral percentage, strength, stiffness, and morphology. Toughness was lower when 1,25(OH)(2)D-3 was used at 21 days, but this effect was not observed at 40 days of age. Bone mineral density was greater when 100% of vitamin D-3 was used at 40 days of age. The reduction of up to 50% of vitamin D-3 levels is sufficient to ensure performance and bone development of broilers at 21 and 40 days of age. The inclusion of 0.5 mu g 1,25(OH)(2)D-3/kg in addition to diets with sufficient levels of vitamin D-3 shows no effect on the improvement of those parameters at the same ages.
Keywords: broilers; growth performance; Solanum glaucophyllum